2018
DOI: 10.1039/c7ta07294e
|View full text |Cite
|
Sign up to set email alerts
|

Metal organic framework based mixed matrix membranes: an overview on filler/polymer interfaces

Abstract: This review focuses on state-of-the-art solutions and strategies for MOF/polymer interface issues in mixed matrix membranes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
270
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 424 publications
(282 citation statements)
references
References 170 publications
1
270
0
1
Order By: Relevance
“…To address the MOF/polymer interface issue, the selection of MOF fillers and polymer matrix pair is of great significance for MMM fabrication as it directly determines their morphology and separation performances . Generally, tight control of the nature of interactions between MOF and the polymer chains can enhance the interface adhesion between these two materials.…”
Section: Selection Of Pair Mof Filler—polymer Matrixmentioning
confidence: 99%
“…To address the MOF/polymer interface issue, the selection of MOF fillers and polymer matrix pair is of great significance for MMM fabrication as it directly determines their morphology and separation performances . Generally, tight control of the nature of interactions between MOF and the polymer chains can enhance the interface adhesion between these two materials.…”
Section: Selection Of Pair Mof Filler—polymer Matrixmentioning
confidence: 99%
“…On the other hand, there are still several technical challenges related with the development of MOF-based MMMs such as pair-wise selection of MOF and polymer, stability and dispersion of MOF in the polymer matrix, existence of the interfacial defects in the MMM. A recent review article summarized these issues together with the possible strategies to improve the compatibility between the filler and polymer using different experimental approaches [80]. In this section, we will specifically focus on a recent advancement in the field of MOF-based MMMs, incorporation of ionic liquids (ILs) as interface agents into the MOF/polymer MMMs to improve filler/polymer interfacial defects and to enhance the gas separation performance of MMMs.…”
Section: Recent Advances In Metal Organic Framework (Mof)-based Mmms mentioning
confidence: 99%
“…It has been discussed that the MOF/polymer compatibility in the MMMs has been reported to be poor and only low MOF filler loadings were achieved before the membrane selectivity is negatively affected [92]. Zhu et al [80] reviewed the existing solutions and strategies utilized to improve MOF/polymer compatibility. The MOF/polymer interface dictates feasibility and stability of MOF/polymer MMMs, therefore fundamental understanding of this interface is critical.…”
Section: Understanding the Mof/polymer Compatibility: The Role Of Commentioning
confidence: 99%
See 1 more Smart Citation
“…23,24 The most important challenges in the formation of advanced mixed-matrix membranes are: (i) elimination of interfacial defects that arise from poor compatibility between the polymer matrix and the highly selective ultramicroporous filler and (ii) limitations in the maximum filler loading for MMMs with sufficiently high mechanical strength. 25 A recent study demonstrated that ZIF-8 nanoparticles coated with polydopamine (PD) enhanced their compatability with a Tröger's base derived polyimide matrix due to interactions by hydrogen bonding of the orthodihydroxyl groups in the PD and the nitrogen of the imidazole in ZIF-8. 26 The resulting MMMs demonstrated moderately improved gas separation properties but no propylene/propane permeation data were reported and the ZIF-8 content was limited to only 30 wt%.…”
Section: Introductionmentioning
confidence: 99%